End of Pandemic Parental Hesitancy Towards Pediatric COVID-19 Vaccination: A Cross-sectional Survey at Two Lebanese Tertiary Hospitals - Sabine Shehab; Lina Anouti; Celina F. Boutros; Christelle Radi; Silma El Baasiri; Arabia Badih; Rawan Korman; Marwa El Masri; Joudie Alwan; Maha Monzer; Yara Bitar; Mona Kassem; et al. (Journal of Epidemiology and Global Health)
Abstract Background This observational prospective cross-sectional study was conducted during the last 4 months of the COVID-19 pandemic to determine whether parental hesitancy to vaccinate their children against COVID-19 had improved compared to earlier studies in other countries showing high levels of hesitancy. Methods: Parents were surveyed from January 4 until May 16, 2023, at two tertiary medical centers in Beirut, the American University of Beirut Medical Center (AUBMC) and the Saint George Hospital University Medical Center (SGHUMC). Results: The study enrolled 950 participants, predominantly mothers (79.6%) aged 30–49 (79%), highly educated parents (69.8% of mothers and 62.2% of fathers were university graduates). Although routine childhood vaccinations received remarkable acceptance (98.3%), there was considerable hesitancy towards pediatric COVID-19 (56.4%). Only 9.4% had vaccinated all eligible children. The main parental concern was the vaccine’s safety and perceived lack of testing (p < 0.001). Other factors were parental gender, vaccination status, and children’s age. In the adjusted model, mothers had a higher rate of vaccine acceptance (AOR: 1.746 [1.059–2.878], p = 0.029). Similarly, parents vaccinated against COVID-19 vaccine (AOR: 2.703, p < 0.001) and parents of children aged 12–17 (AOR: 4.450, p < 0.001) had more vaccine acceptance. Conclusion: This study’s findings indicate a persistently high level of hesitancy for pediatric COVID-19 vaccination despite more than two years of positive global experience with the vaccine. Raising awareness about the safety and effectiveness of pediatric COVID-19 vaccination would address this hesitancy and mitigate the impact of COVID-19 on children’s health and well-being.